Sunni dan Syi'ah: Dinamika Sejarah dan Tantangan dalam Membangun Peradaban Islam Global - Natasya Farhati Yunis; Lailatul Barqah; Eliya Roza (Fakultas Adab dan Ilmu Budaya UIN Sunan Kalijaga Yogyakarta, 2025)
Abstract: This research aims to examine the historical dynamics as well as the roles and challenges of Sunni and Shi'a in building a global Islamic civilization. Sunni and Shi'a as two major sects often have different views and often contradict each other. In addition to cooperation, it is not uncommon for conflicts to decorate the relationship between these two schools. This research is a qualitative research using a literature review. This study shows that historically, Sunni-Shi'a differences began with leadership disputes after the death of the Prophet Muhammad (PBUH), which later developed into theological, ideological, and practical differences. The main difference between the two lies in the concept of leadership (caliphate vs. imamah), the source of law, and the view of the Prophet's companions. Conflicts between Sunnis and Shi'ites are often triggered by political and geopolitical factors. However, efforts for dialogue, educational reform, and cross-sectarian cooperation also continue to be carried out for the sake of harmonization of relations. Furthermore, the dynamics of relations between Sunnis and Shi'a are not solely antagonistic. History records that in addition to conflicts, there were also periods of collaboration and mutual influence between the two, both in the intellectual and cultural fields. These two schools played an important role in building the Islamic scientific tradition. In the context of an increasingly connected and complex world, the challenges faced by Muslims require cross-sectarian solidarity, not sharpening differences. Thus, the future of global Islamic civilization will be largely determined by the ability of Sunnis and Shi'a to understand, respect, and work together for the common good. Abstrak: Penelitian ini bertujuan untuk mengkaji dinamika sejarah serta peran dan tantangan sunni dan syi’ah dalam membangun peradaban Islam global. Sunni dan syi’ah sebagai dua aliran besar kerap memiliki perbedaan pandangan dan sering bertentangan. Selain kerjasama, tak jarang konflik menghiasi hubungan kedua aliran ini. Penelitian ini merupakan penelitian kualitatif dengan menggunakan kajian kepustakaan. Penelitian ini menunjukkan bahwa secara historis, perbedaan Sunni-Syi’ah bermula dari sengketa kepemimpinan pasca wafatnya Nabi Muhammad SAW, yang kemudian berkembang menjadi perbedaan teologis, ideologis, dan praktik keagamaan. Perbedaan utama antara keduanya terletak pada konsep kepemimpinan (khilafah vs. imamah), sumber hukum, dan pandangan terhadap sahabat Nabi. Adapun konflik antara Sunni dan Syi’ah seringkali dipicu oleh faktor politik dan geopolitik. Namun demikian, upaya dialog, reformasi pendidikan, dan kerja sama lintas mazhab juga terus dilakukan demi harmonisasi hubungan. Lebih jauh, dinamika hubungan antara Sunni dan Syi’ah tidak semata-mata bersifat antagonistik. Sejarah mencatat bahwa selain konflik, terdapat pula masa-masa kolaborasi dan saling pengaruh di antara keduanya, baik dalam bidang intelektual maupun budaya. Kedua mazhab ini berperan penting dalam membangun tradisi keilmuan Islam. Dalam konteks dunia yang semakin terhubung dan kompleks, tantangan yang dihadapi umat Islam membutuhkan solidaritas lintas mazhab, bukan justru mempertajam perbedaan. Dengan demikian, masa depan peradaban Islam global akan sangat ditentukan oleh kemampuan Sunni dan Syi’ah untuk saling memahami, menghargai, dan bekerja sama demi kemaslahatan bersama.